Radicular Cyst in Deciduous Maxillary Molars: A Rarity - Shetty, Shibani (Humana Press Inc, 2009)
Radicular cyst arising from deciduous teeth is exceedingly rare accounting for <1% of all radicular cysts. A total of 122 cases have been reported to date in the English language literature. We present a rare case of a radicular cyst associated with a decayed deciduous maxillary molar tooth without any history of prior pulp therapy. Our aim is to emphasize the recognition of inflammatory radicular lesions associated with deciduous teeth which may adversely impact underlying permanent successor.